Whole brain snapshot CEST at 3T using 3D-EPI: Aiming for speed, volume, and homogeneity - Mueller, Sebastian; Stirnberg, Rüdiger; Akbey, Suzan; Ehses, Philipp; Scheffler, Klaus; Stöcker, Tony; Zaiß, Moritz (Magnetic Resonance in Medicine, 2020)
Purpose: CEST MRI enables imaging of distributions of low-concentrated metabolites as well as proteins and peptides and their alterations in diseases. CEST examinations often suffer from low spatial resolution, long acquisition times, and concomitant motion artifacts. This work aims to maximize both resolution and volume coverage with a 3D-EPI snapshot CEST approach at 3T, allowing for fast and robust whole-brain CEST MRI. Methods: Resolution and temporal SNR of 3D-EPI examinations with nonselective excitation were optimized at a clinical 3T MR scanner in five healthy subjects using a clinical head/neck coil. A CEST presaturation module for low power relayed nuclear Overhauser enhancement and amide proton transfer contrast was applied as an example. The suggested postprocessing included motion correction, dynamic B0 correction, denoising, and B1 correction and was compared to an established 3D-gradient echo-based sequence. Results: CEST examinations were performed at 1.8 mm nominal isotropic resolution in 4.3 s per presaturation offset. In contrast to slab-selective 3D or multislice approaches, the whole brain was covered. Repeated examinations at three different B1 values took 13 minutes for 58 presaturation offsets with temporal SNR around 75. The resulting CEST effects revealed significant gray and white matter contrast and were of similar quality across the whole brain. Coefficient of variation across three healthy subjects was below 9%. Conclusion: The suggested protocol enables whole brain coverage at 1.8 mm isotropic resolution and fast acquisition of 4.3 s per presaturation offset. For the fitted CEST amplitudes, high reproducibility was proven, increasing the opportunities of quantitative CEST investigations at 3T significantly.
CRIS-Team Scopus Importer:2020-05-19
Keywords: 3D CEST MRI; chemical exchange saturation transfer MRI 3T; chemical exchange saturation transfer MRI EPI; high resolution CEST MRI; whole-brain CEST MRI